Application of flipped classroom combined with problem-based learning - An effective learning approach to upgrade learning in medical students: A randomized controlled trial - Jayasree Palla; Sindhura Moparthi; Sateesh Babu Kaki; Ravi Babu Komaram (MRIMS Journal of Health Sciences, 2024)
Background: As per the recent advancement in medicine, novel learning methodological innovations such as flipped classroom (FC) and problem-based learning (PBL) have earned ample recognition in medical education. The present study was directed with an aim to assess the effectiveness of combined learning method (CLM: FC combined with PBL) over traditional lecture-based classroom (TLC). Objectives: The objectives of this study were as follows: to determine whether CLM improves learning outcome among medical students and to determine whether there is any significant difference in students' perceptions regarding learning method implemented. Materials and Methods: A randomized controlled trial (educational interventional study) was conducted with 100 medical students; they were randomly allocated into two equal groups: experimental group (EG) was taught by CLM, whereas control group (CG) was taught by TLC method. Closed- and open-ended questionnaire was used for the collection of data. Statistical analysis was done by applying independent samples t-test and Chi-square test. Results: A significant difference in the learning outcome was observed between the mean posttest scores of the two groups (CG = 31.5, EG = 46.2). There was a significant difference in the mean scores of perception between the groups (P ≤ 0.05). Chi-square test showed that students' satisfaction is associated with the CLM (P = 0.00001). Conclusion: FC combined with PBL can be considered a better alternative to the lecture-based classroom for educating medical students on maternal and child health care.